Increased serum piwi-interacting RNAs as a novel potential diagnostic tool for brucellosis - Wang, Cheng; Zhang, Cuiping; Fu, Quan; Zhang, Nan; Ding, Meng; Zhou, Zhen; Chen, Xi; Zhang, Fengmin; Zhang, Chunni; Zhang, Chen-Yu; Wang, Jun-Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Piwi-interacting RNAs (piRNAs) have emerged as potential novel indicators for various diseases; however, their diagnostic value for brucellosis remains unclear. This study aimed to evaluate the diagnostic potential of altered serum piRNAs in patients with brucellosis. Methods: Illumina sequencing via synthesis (SBS) technology was used to screen the serum piRNA profile in brucellosis patients, and markedly dysregulated piRNAs were confirmed by quantitative real-time polymerase chain reaction (qRT-PCR) assay in two sets from a cohort of 73 brucellosis patients and 65 controls. Results: Illumina SBS technology results showed that seven piRNAs were markedly elevated in brucellosis patients compared to normal controls. The seven upregulated piRNAs were further validated individually by qRT-PCR, of which three piRNAs (piR-000753, piR-001312, and piR-016742) were confirmed to be significantly and steadily increased in the patients (> 2-fold, P < 0.01). The area under the receiver operating characteristic (ROC) curve (AUCs) for the three piRNAs ranged from 0.698 to 0.783. The AUC for the three piRNAs combination was 0.772, with a specificity of 86% and a positive predictive value of 90%, respectively. Conclusions: The three-piRNA panel identified in this study has potential as a novel blood-based auxiliary tool for brucellosis detection.